Development and characterizations of mycelium-based composites - Davis, Morgan N., author; Li, Yan Vivian, advisor; Morris, Kristen, committee member; Stewart, Jane, committee member (Colorado State University. Libraries, 2024)
The current materials economy produces linear materials without regard to their end of life. As the demand for these materials rises, the demand for a new textile economy increases: regenerative by design, minimizing resource input, and waste systems. Mycelium-based composites (MBC) is a lightweight biodegradable material, with good thermal insulation, fire resistance, and acoustic attenuation. The role of MBC lies at a crossroads between biology and design, where designers incorporate biological principles and need to understand the mechanisms of material growth. The study's specific aims include the evaluation of the chemical, mechanical, and physical properties of MBC developed in various conditions and nutrient substrates. Essential to this process is the cultivation of the mycelium, where careful considerations of fungal species, nutrient substrate, and growing parameters are critical. A component of the first critical factor emerges: verification of the fungal DNA. The nutrient substrate hemp fabric demonstrates great compatibility, with the fungal species Pleurotus fossulatus, as it has the largest hyphae diameter, and offers solutions to incorporate waste. In contrast to the strong hydrophilic nature inherent in many natural cellose, mycelium exhibits hydrophobic properties, a critical feature in terms of product implication. The results provide insight for the future design and optimization of mycelium-based composites for product development innovation.
Keywords: composite; product development; bio material; sustainability; mycelium